Factors associated with unfavourable outcome after Burr Hole drainage in Subdural Hematoma (SDH) at Sanglah General Hospital, Bali, Indonesia - I Gusti Ngurah Purnomo; I Wayan Niryana; Nyoman Golden (Intisari Sains Medis, 2020)
Background: Subdural hematoma is a neurosurgical disorder that often occurs in the elderly with simple, relatively fast and minimally invasive surgical therapy, but has a high postoperative mortality rate due to unfavourable outcome. This study aims to evaluate factors associated with unfavourable outcome after burr hole drainage in a subdural hematoma (SDH) at Sanglah General Hospital, Bali, Indonesia.Method: A prospective cohort study was conducted among 60 respondents to determine factors influencing the outcome of patients with subdural hematoma after burr hole drainage.  The independent variables in this study included age, comorbid factors, trauma onset, GCS, hematoma thickness, and midline shift.  Dependent variables include the Glasgow Outcome Scale (GOS), which is divided into 2 groups, favourable outcome, and unfavourable outcome. Data were analyzed using SPSS version 17 for Windows.Results: There were 19 respondents (31.7%) had unfavourable outcomes and 41 respondents (68.3%) had favourable outcomes.  From the bivariate analysis, significant associated risk factors were found in the onset of trauma (p=0.048), GCS (p=0.000), hematoma thickness (p = 0.000), and midline shift (p=0.000).  From the multivariate analysis, it was found that low GCS was the most dominant risk factor for the unfavourable outcome following burr hole drainage (OR=22.30; 95% CI= 2.22-223.80; p=0.008) Conclusion: This study concludes that low GCS was the most dominant risk factor for unfavourable outcome in patients with subdural hematoma after burr hole drainage